2017
DOI: 10.1515/aoa-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Noise Level Dissemination Surrounding Mining and Industrial Areas of Keonjhar, Odisha: a Comprehensive Approach Using Noise Mapping

Abstract: Noise mapping is a well-established practice among the European nations, and it has been follow for almost two decades. Recently, as per guidelines of the Directorate General of Mines Safety (DGMS), India, noise mapping has been made mandatory in the mining expanses. This study is an effort to map the noise levels in nearby areas of mines in the northern Keonjhar district. The motive of this study is to quantify the existing A-weighted time-average sound level (L Aeq, T ) in the study area to probe its effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Except for one study that takes place in the construction field (Lee, Kim, & Hong, 2019), every other paper set is related to the mining industry, where the exploited commodities varied between marble (Melo Neto, Kohlman Rabbani, Barkokébas Junior, Lago, & Jonathas, 2012) to aggregates (Onder, Onder, & Mutlu, 2012) and andesite (Kosała & Stępień, 2016), limestone (Çınar & Şensöğüt, 2019), coal (Simion, Kovacs, Toth, Ilie, & Gireadă, 2017) and lignite (Srivastava, Gupta, Srivastava, & Kaur, 2010), chromite (Kerketta, Gartia, & Bagh, 2012), copper (Lilic et al, 2018) and iron (Lokhande et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for one study that takes place in the construction field (Lee, Kim, & Hong, 2019), every other paper set is related to the mining industry, where the exploited commodities varied between marble (Melo Neto, Kohlman Rabbani, Barkokébas Junior, Lago, & Jonathas, 2012) to aggregates (Onder, Onder, & Mutlu, 2012) and andesite (Kosała & Stępień, 2016), limestone (Çınar & Şensöğüt, 2019), coal (Simion, Kovacs, Toth, Ilie, & Gireadă, 2017) and lignite (Srivastava, Gupta, Srivastava, & Kaur, 2010), chromite (Kerketta, Gartia, & Bagh, 2012), copper (Lilic et al, 2018) and iron (Lokhande et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Given that this study's aim is related to occupational exposure to noise, the experimental data was classified according to the measurement setting, which is provided in Table 1, divided into activity, equipment, job category, and working area. (Srivastava et al, 2010) x (Gupta, Roy, & A. Rajan B, 2012) x (Kerketta et al, 2012) x (Melo Neto et al, 2012) x (Onder et al, 2012) x (Cinar & Sensogut, 2013) x (Gyamfi, Amankwaa, Owusu Sekyere, & Boateng, 2016) x (Kosała & Stępień, 2016) x x (Lokhande et al, 2017) x (Simion et al, 2017) x (Lilic et al, 2018) x (Wichers et al, 2018) x (Çınar & Şensöğüt, 2019) (Lee et al, 2019) x (Mihut, 2019) x…”
Section: Resultsmentioning
confidence: 99%
“…Analyses are carried out in line with numerical simulations in the process of strategic noise mapping and action plans. In the literature, various noise mapping software are used in noise mapping simulations and it is observed that the most widely used noise mapping programs are SoundPLAN [ 12 , 14 , 17 , 18 , 23 , 25 , 47 – 50 ], CadnaA [ 15 , 19 21 , 51 , 52 ], and Predictor [ 16 , 36 , 53 ]. In the research of Butorina et al [ 12 ], SoundPLAN noise mapping software was used to analyze noise level, increasing the efficiency of the noise protection design process was carried out with the application of building information modeling (BIM).…”
Section: The Strategic Noise Mapping Process Based On Industrial Noisementioning
confidence: 99%
“…In the research, the development of the building information model was obtained using the data exchange between SoundPLAN, AutoCAD 3D, or Revit and Navisworks. In the research of Lokhande et al [ 53 ], noise level analyses were performed surrounding mining and industrial areas of Keonjhar, and noise maps are prepared using Predictor LimA Software and other GIS tools. In the study of Jung et al [ 52 ], it was stated that noise maps were prepared with CadnaA software that is widely used for environmental impact assessments.…”
Section: The Strategic Noise Mapping Process Based On Industrial Noisementioning
confidence: 99%
See 1 more Smart Citation